A Gricean Maxim Analysis in Teaching and Learning Process at Higher Level Education - Sepri Kurniadi (LPPM Politeknik Aceh Selatan, 2021)
This study was aimed at identifying the maxim violation(s) in English classroom in an English class at Politeknik Aceh Selatan. The maxim violation analyzed was only the one produced by the lecturer as the key speaker in the video. Regarding the methodology, this study employed qualitative approach because the analysis emphasized more on the data quality instead of data quantity. The data source as well as the instrument for this study was the video from English class and the data collection was carried out through a documentation procedure in which the video were checked repeatedly to classify data based on the utterances. The data were then analyzed using Interactive Analysis following the three-step procedures: data condensation, data display, and data verification The results showed that the most Gricean Maximum violations occured in the quantity maxim (42 times). The second is the maxim of quality (24 times) and the maximum of relation (17 times). The least violations occur in the maxim of manner (5 times).